2020
DOI: 10.1001/jama.2020.9482
|View full text |Cite
|
Sign up to set email alerts
|

Association of Menopausal Hormone Therapy With Breast Cancer Incidence and Mortality During Long-term Follow-up of the Women’s Health Initiative Randomized Clinical Trials

Abstract: The influence of menopausal hormone therapy on breast cancer remains unsettled with discordant findings from observational studies and randomized clinical trials.OBJECTIVE To assess the association of prior randomized use of estrogen plus progestin or prior randomized use of estrogen alone with breast cancer incidence and mortality in the Women's Health Initiative clinical trials. DESIGN, SETTING, AND PARTICIPANTSLong-term follow-up of 2 placebo-controlled randomized clinical trials that involved 27 347 postme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
277
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 278 publications
(297 citation statements)
references
References 39 publications
9
277
3
8
Order By: Relevance
“…Indian data are sparse on the use of MHT; hence, this section is based on the guidelines developed by various societies. [ 8 147 148 149 150 151 ]…”
Section: Anagement O Ptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indian data are sparse on the use of MHT; hence, this section is based on the guidelines developed by various societies. [ 8 147 148 149 150 151 ]…”
Section: Anagement O Ptionsmentioning
confidence: 99%
“…259. In the WHI trial, prior randomized use of CEE plus MPA, compared with placebo, among women who had an intact uterus, was significantly associated with a higher breast cancer incidence but no significant difference in breast cancer mortality[ 151 ]…”
Section: Onclusions On the R Isks And mentioning
confidence: 99%
“…However, whilst reduction of risk is of benefit, none of the trials to date have shown a survival benefit. This has led to the suggestion that premarin should be used for women at least 5 years post-menopausal and without a uterus, since in this group the Women’s Health Initiative trial use was associated with a survival advantage [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to another assertion made by DeSantis and Siegel, there is information regarding longer‐term breast cancer risk among women in a combined HT trial who infrequently used systemic hormones after the intervention. In that study, a median of 5.6 years of CEE + MPA use sustained a statistically significant increase in breast cancer incidence through a median cumulative follow‐up of 13 years initially 3 and now 20 years 10 . On a population level, as combined HT use continues to occur at a low level, many women now entering menopause no longer experience the long‐term increase in the risk of breast cancer observed with combined HT use.…”
mentioning
confidence: 89%